Catalisadores à base de Cu, Co ou Fe trocados ou suportados em zeólita USY avaliação na redução de NO com CO - Silva, Edilene Deise da (2008)
The emissions of the nitrogen oxides (NOx) must be hardly reduced in the next years. The catalytic reduction of NO with CO is one of the possible processes with potential to be able to transform those oxides in N2. In that process, supported noble metals have been the most used, however, their low stability in the presence of water steam or SO2, have led to develop studies to overcome those limitations. Perovkites type catalysts or transition metal oxides supported in a variety of support show activity in this reaction. Nevertheless, no adequate information about the activity of metal oxides supported on zeolites is found in the literature. In this context, the present work was focused to prepare and evaluate between 150°C and 500°C, Cu, Co or Fe containing catalysts dispersed on USY (Si/Al=3,4) or ZSM-5 (Si/Al=12,8) zeolites in the reduction of NO with CO and in the oxidation of CO to CO2. The oxide activity was also compared with that of the respective metal cations located in charge compensation sites. The catalysts were prepared by ion exchange or impregnation and characterized by AAS, XRD, DRS-UV and H2-TPR. Conversion data of NO to N2 on USY and ZSM-5 zeolites containing predominantly Cu2+ or Co2+ cations in exchangeable sites were more active when located on ZSM-5 zeolite (MFI structure), with the Cu2+ cations being more active. On the other hand, Cu, Co or Fe oxides supported on USY or ZSM-5 were more active than cations of considered metals in exchangeable sites, with conversion being dependent on the type and metal content and the type of zeolite. Among the studied metal oxides, the Fe one was the most active and selective. However the presence of O2 or water steam in the feed inhibited the NO reduction with CO on Fe oxide, which was attributed to the deactivation of the active sites by the water steam and the CO direct oxidation by O2 occurring preferentially than CO oxidation via NO reduction. This result gives evidence of the water steam leads to the deactivation of the metallic active sites and O2 favors the direct oxidation of CO to CO2 in detriment of its oxidation by NO reduction. The NO conversion was not significantly affected by the presence of SO2 in the feed (40 ppm).